Vortex phases in type-I superconductors - Sweeney, Mark Charles, author; Gelfand, Martin Paul, advisor; Mueller, Jennifer L., committee member; Bradley, Richard M., committee member; Field, Stuart B., committee member (Colorado State University. Libraries, 2010)
Sufficiently thin films of type-I superconductor in a perpendicular magnetic field exhibit a triangular vortex lattice, while thick films develop an intermediate state. To elucidate what happens between these two regimes, precise numerical calculations have been made within Ginzburg-Landau theory at κ=0.5 and 0.25 for a variety of vortex lattice structures with one flux quantum per unit cell. The phase diagram in the space of mean induction and film thickness includes a narrow wedge in which a square lattice is stable, surrounded by the domain of stability of the triangular lattice at thinner films/lower fields and, on the other side, rectangular lattices with continuously varying aspect ratio. The vortex lattice has an anomalously small shear modulus within and close to the square lattice phase. Solutions of the Ginzburg-Landau equations have also been obtained for bulk systems and thin films for vortex lattices with one vortex but two flux quanta per square or triangular unit cell. These lattices of double fluxoid vortices are thermodynamically unstable in bulk in both type-I and type-II superconductors, as expected. In type-I films the situation is less clear, because the corresponding calculations for more complicated vortex lattice structures are not yet possible.
Keywords: superconductors; Vortex-motion; Thin films; Superconductivity; Superconductors -- Magnetic fields